Increasing the Efficiency of Police Departments in Allegany County, New York, 1994-1995 - Hall, William ([Verlag nicht ermittelbar], 2000)
This study sought to investigate the attitudes of residents and law enforcement personnel living or working in Allegany County, New York in order to (1) assess community support of law enforcement efforts to collaborate on projects, and (2) determine rural law enforcement agencies' willingness to work together on community policing projects and share resources in such a way as to improve and increase their overall individual and collective effectiveness and efficiency. Community policing, for this study, was defined as any law enforcement strategy designed to improve policy directed toward law enforcement interaction with community groups and citizens. Data were gathered from surveys that were distributed to two groups. First, to determine community perceptions of crime and attitudes toward the development of collaborative community policing strategies, surveys were distributed to the residents of the villages of Alfred and Wellsville and the town of Alfred in Allegany County, New York (Part 1, Community Survey Data). Second, to capture the ideas and perceptions of different types of law enforcement agencies regarding their willingness to share training, communication, and technology, surveys were distributed to the law enforcement agencies of Wellsville, Alfred, the New York State Police substation (located in the town of Wellsville), the county sheriff's department, and the Alfred State College and Alfred University public safety departments (Part 2, Law Enforcement Survey Data). For Part 1 (Community Survey Data), the residents were asked to rate their level of fear of crime, the reason for most crime problems (i.e., gangs, drugs, or unsupervised children), positive and negative contact with police, the presence and overall level of police service in the neighborhoods, and the importance of motor vehicle patrols, foot patrols, crime prevention programs, and traffic enforcement. Respondents were also asked whether they agreed that police should concentrate more on catching criminals (as opposed to implementing community-based programs), and if community policing was a good idea. Demographic data on residents includes their age, sex, whether they had been the victim of a property or personal crime, and the number of years they had lived in their respective communities. Demographic information for Part 2 (Law Enforcement Survey Data) includes the sex, age, and educational level of law enforcement respondents, as well as the number of years they had worked with their respective departments. Respondents were asked if they believed in and would support programs targeted toward youth, adults, the elderly, and merchants. Further queries focused on the number of regular and overtime hours used to train, develop, and implement department programs. A series of questions dealing with degrees of trust between the departments and levels of optimism was also asked to gauge attitudes that might discourage collaboration efforts with other departments on community-oriented programs. Officers were also asked to rate their willingness to work with the other agencies.